Effect of quadrantwise versus full‐mouth subgingival instrumentation on clinical and microbiological parameters in periodontitis patients: A randomized clinical trial - Isola, Gaetano; Polizzi, Alessandro; Santonocito, Simona; Alibrandi, Angela; Pesce, Paolo; Kocher, Thomas (Journal of periodontal research, 2024)
Aim This study evaluated the efficacy of quadrantwise subgingival instrumentation (Q‐SI) versus one‐stage full‐mouth subgingival instrumentation (FM‐SI) on probing depth and periodontal pathogen reduction over a 6‐month follow‐up period, as well as whether baseline periodontal pathogens influenced the impact of periodontal treatment protocols on outcomes. Methods Patients with periodontitis were randomized to receive Q‐SI (n = 43) or FM‐SI (n = 45). Patients were instructed and motivated to maintain optimal oral hygiene during the treatment sessions. Clinical (probing pocket depth [PPD], clinical attachment loss [CAL], and bleeding on probing [BOP]) and periodontal pathogens were assessed at baseline and after 30, 90, and 180 days. Total bacterial load and periodontal pathogens were analysed via real‐time PCR. Results At the 6‐month follow‐up, the median PPD decreased from 4.8 mm (interquartile range [IQR]: 4.3–5.2) to 2.6 mm (IQR: 2.3–2.9) in FM‐SI patients and from 4.7 mm (IQR: 4.1–5.2) to 3.2 mm (IQR: 2.4–3.5) in Q‐SI patients (p < .001). At 6 months, FM‐SI was more effective at reducing the median proportions of Porphyromonas gingivalis (Pg), Aggregatibacter actinocomyctemcomitans, and Tannerella forsythia (Tf) (p < .001 for each value). Multilevel linear regression analysis demonstrated that high baseline PPD (p = .029), Pg (p = .014), and Tf (p < .001) levels and the FM‐SI protocol (p < .001) were statistically significant predictors of PPD reduction at 6 months. Furthermore, PPD reduction was significantly greater in the FM‐SI group when lower baseline Pg levels were detected. Conclusion The FM‐SI was more effective than the Q‐SI in reducing the mean PPD and number of periodontal pathogens in periodontitis patients over a 6‐month follow‐up period. Higher baseline PPD and Pg levels had a negative impact on PPD reduction at 6 months after FM‐SI.